Pemeliharaan dan Perawatan Arsip Statis di Kantor Arsip Kabupaten Pesisir Selatan - Gusda, Aldona; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
The purpose of this paper to describe the maintenance and care of archive in the Library Archives and Documentation Office of Pesisir Selatan and the obstacles encountered in the maintenance and care of archive in the Library Archives and Documentation Office of the South Coastal District and what efforts were made ​​in the maintenance and care of static archive in office of Library Archives and Documentation Pesisir Selatan. Method in this study uses descriptive method, to obtain the data the authors conducted observations and interviews. The object to be studied is the maintenance and care of archive in the Library Archives and Documentation Office of the Pesisir Selatan. Based on the results of this study concluded that the maintenance and care of the static archive in the Office of Archives and Documentation Library Pesisir Selatan has not done well because it is still using the traditional maintenance process. Keywords: maintenance of archives; archival